Specific Biological Features of Adipose Tissue, and Their Impact on HIV Persistence - Bourgeois, Christine; Gorwood, Jennifer; Barrail-Tran, Aurélie; Lagathu, Claire; Capeau, Jacqueline; Desjardins, Delphine; Le Grand, Roger; Damouche, Abderaouf; Béréziat, Véronique; Lambotte, Olivier (Frontiers in Microbiology, 2019)
Although it has long been known that adipose tissue (AT) is involved in infection, interest in this topic is now growing. Although white AT can contribute to anti-infectious immune responses, it can also be targeted and perturbed by pathogens. The AT’s immune involvement is primarily due to strong pro-inflammatory responses (with both local and paracrine effects), and the large number of fat-resident macrophages. Adipocytes also exert direct antimicrobial responses. In recent years, it has been found that memory T cells accumulate in AT, where they provide efficient secondary responses against viral pathogens. These observations has prompted researchers to re-evaluate the links between obesity and susceptibility to infections. In contrast, AT serves as a reservoir for several persistence pathogens, such as human adenovirus Ad-36, Trypanosoma gondii, Mycobacterium tuberculosis, influenza A virus, and cytomegalovirus (CMV). The presence and persistence of bacterial DNA in AT has led to the concept of a tissue-specific microbiota. The unexpected coexistence of immune cells and pathogens within the specific AT environment is intriguing, and its impact on anti-infectious immune responses requires further evaluation. Adipose tissue has been recently identified as a site of HIV persistence. In the context of HIV infection, AT is targeted by both the virus and the antiretroviral drugs. Adipose tissue’s intrinsic metabolic features, large overall mass and wide distribution make it a major tissue reservoir, and one that may contribute to the pathophysiology of chronic HIV infections. Here, we review the immune, metabolic, viral and pharmacological aspects that contribute to HIV persistence in AT. We also evaluate the respective impacts of both intrinsic and HIV-induced factors on AT’s involvement as a viral reservoir. Lastly, we examine the potential consequences of HIV persistence on the metabolic and immune activities of AT.